Implementation of Psychomotor Assessment in Islamic Religious Education: An Instrumental Case Study in Indonesian Elementary Schools: Teachers’ Understanding of Psychomotor Assessment, Planning of Psychomotor Assessment, Strategies and Techniques of Psychomotor Assessment - Alya Muti'ah Setiani; Saepul Anwar; Mohammad Rindu Fajar Islamy (Elementary Teacher Education Program, Majalengka University, 2026)
Psychomotor assessment in Islamic Religious Education (IRE) at the elementary school level is essential for ensuring that students' religious understanding extends beyond cognitive knowledge to encompass practical worship skills. This study aims to analyze the implementation of psychomotor assessment in IRE learning at a public elementary school in Bandung, Indonesia, examining teachers' understanding, assessment planning, and implementation strategies. A descriptive qualitative approach with an instrumental case study design was employed. Data were collected through semi-structured interviews with 3 IRE teachers, non-participant classroom observations (12 sessions), and document analysis of assessment instruments and student portfolios. Data were analyzed thematically using Miles and Huberman's interactive model, involving data reduction, display, and verification. Teachers conceptualized psychomotor assessment as authentic evaluation of worship practices integrated with character development. Assessment planning systematically translated curriculum objectives into observable performance indicators using criterion-referenced rubrics. Implementation strategies combined direct observation (70%), practice simulations (20%), and peer assessment (10%), with multiple assessment points ensuring reliability. Assessment data informed formative feedback, differentiated instruction, and curriculum refinement. Professional development occurred through formal training programs (twice annually), peer collaboration networks, and self-directed learning initiatives. The study demonstrates a comprehensive psychomotor assessment system that effectively bridges theoretical knowledge and practical application in IRE. Findings suggest the need for standardized assessment rubrics, sustained practical training programs, and systematic documentation protocols to enhance assessment validity and pedagogical impact in religious education contexts.